2020
DOI: 10.3390/socsci9040046
|View full text |Cite
|
Sign up to set email alerts
|

Minority Stress and Mental Health in Italian Bisexual People

Abstract: Bisexual people are a strongly stigmatized population experiencing health disparities caused by social stigmatization. The predominant framework helping to understand these health disparities and the impact of stigma on mental health of social groups belonging to a sexual minority identity constitutes the minority stress theory. In Italy, studies assessing this model in bisexual populations are very limited. Within this framework, the current study aimed at assessing in 381 Italian bisexual individuals (62 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
(94 reference statements)
4
19
0
Order By: Relevance
“…Generally speaking, the Taiwanese and Italian cultures are significantly differentiated according to their respective collective versus individualistic attitudes. Although both cultures tend to stigmatize LGB+ people (Hu et al, 2019;Huang, Chan, & Cui, 2020a;Huang, Luo, et al, 2020b;Picariello et al, 2019;Scandurra et al, 2020), their attitudinal differences may influence how the MS experienced by LGB+ people affects their health. Indeed, individualistic and collective cultures predict different individual efforts to achieve societal approval: Individualistic cultures emphasize individual achievement and uniqueness while collective cultures emphasize social connectedness and harmony (Sattler & Lemke, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the Taiwanese and Italian cultures are significantly differentiated according to their respective collective versus individualistic attitudes. Although both cultures tend to stigmatize LGB+ people (Hu et al, 2019;Huang, Chan, & Cui, 2020a;Huang, Luo, et al, 2020b;Picariello et al, 2019;Scandurra et al, 2020), their attitudinal differences may influence how the MS experienced by LGB+ people affects their health. Indeed, individualistic and collective cultures predict different individual efforts to achieve societal approval: Individualistic cultures emphasize individual achievement and uniqueness while collective cultures emphasize social connectedness and harmony (Sattler & Lemke, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, although the Italian society seems increasingly accepting of LGB+ individuals (Lingiardi et al, 2016), many recent Italian studies have detected moderate levels of discrimination against this population (Baiocco & Pistella, 2019;Petrocchi et al, 2020;Picariello, Scandurra, Schwartz, & Amodeo, 2019;Scandurra et al, 2020). In Italy, LGB people still face heterosexism in several contexts, such as school, sports, and family: No current legislation to protect people from homophobic harassment and discrimination, and there is little or no visibility of LGB+ people and relationships in many institutions (Baiocco & Pistella, 2019).…”
mentioning
confidence: 99%
“…Clinicians should be aware that bisexual women may face additional prejudice and suffer from higher levels of ISS, relative to lesbian women; however, it is important that clinicians focus on strengthening and promoting a positive LB identification in both LB women. In most clinical settings, psychotherapists working with LB clients aim at reducing ISS and helping clients to alleviate the negative effect that minority stress can have on CO process, working on negative emotions associated with stigmatizing experiences and developing a positive self-image ( Scandurra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, it is conceivable that young people with a high level of ISS are less likely to CO ( Durso and Meyer, 2013 ). It is important to note that recent studies have found that minority stress causes more psychological distress for LB women, relative to other sexual minorities, suggesting that there is a need for more in-depth research into minority stress among these populations ( Prell and Traeen, 2018 ; Scandurra et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation